Electrostatic coupling and interface intermixing in ferroelectric superlattices - Chew, Khian Hooi; Iwata, M.; Lim, K.G.; Ong, L.H. (2012)
A thermodynamic model is developed to study electrostatic coupling and interface intermixing in superlattices comprising alternate layers of ferroelectrics and paraelectrics. Interface intermixing leads to inhomogeneous internal electric field and polarization in superlattices. The spatial distribution of polarization extends into the layer over a distance governed by its correlation length. Periodic modulation of the internal electric field and polarization in superlattices are correlated. Interface intermixing enhances the depolarization field of superlattices; however, it has a negligible effect on polarization and transition temperature. The internal electric field, originating from the electrostatic coupling between ferroelectric layers, plays a dominant role in determining the properties of superlattices. Copyright (C) EPLA, 2012